Diagnostik der sekundären Hypertonie: An was ist bei wem zu denken? - Vonend, Oliver (DMW - Deutsche Medizinische Wochenschrift, 2020)
The prevalence of arterial hypertension with its cardiovascular diseases like myocardial infarction, stroke, chronic kidney disease and peripheral artery disease is increasing in our aging population. Despite numerous efficient and well-tolerated antihypertensive drugs more than eight million people die worldwide from the consequences of insufficiently controlled hypertension every year. One third of the german adult population suffers from high blood pressure. The fact that in only 50 % of hypertonic patients the blood pressure is on a string is even more disturbing. Several factors can counteract sufficient blood pressure control. This article should help to identify patients with possible secondary hypertension. It is certainly not decisive to request a broad screening for all hypertensive patients. A certain pre-selection of potential patients is mandatory. The most common types of secondary hypertension are discussed and the diagnostic and therapeutic pathways are specified.
Keywords: schwer einstellbare Hypertonie; sekundäre Hypertonie; Nierenarterienstenose; primärer Hyperaldosteronismus